Kinesisk yoga? Sinificering af yoga-begrebet i sinologiske, terapeutiske og nyreligiøse sammenhænge (Aura: Journal for the Study of New Religions, 2021)
This article provides a conceptual history (Begriffsgeschichte) of the use of the word yoga in the context of both scientific, therapeutic, and religious approaches to Chinese cultural history, with a focus on somatic practices commonly associated with Daoist traditions. Under the heading Chinese yoga, the author investigates how historical practices such as neidan, daoyin, kaimen, zhanzhuang, gusha, fangzhongshu as well as new therapeutic innovations are referred to as types of yoga such as Taoist yoga, meridian yoga, yin yoga, and sexual yoga. The article traces the origins of variations of the concept of Chinese yoga to the 1920s and 1930s in publications by Richard Wilhelm and C. G. Jung, Cary F. Baynes, and Arthur Waley, follows its reception in the hippie milieu of the 1960s and 1970s, and demonstrates how references to various forms of Chinese yoga have been, and are still being used in both academic research, and therapeutic and new religious milieus.